Descripción de un especie nueva de Creugas Thorell (Araneae: Corinnidae) de la península de Baja California, México - Jiménez, María Luisa (Instituto de Ecología, A.C., 2007)
A new species of running spider, collected in oases of Baja California Sur is described and illustrated.